Election Prediction Using Big Data Analytics-A Survey - Manan koli, Abdul; Ahmed, Muqeem; ., . (International Journal of Engineering and Technology, 2018)
Social media has received much attention due to it's real-time and interactive nature for political discourse, especially around election times. Recently studies have explored the power of social media platforms such as Twitter or Facebook, on recording current social trends and predicting the voting outcomes of an area. These social media generate a large amount of raw data that can be used in decision making for election predictions. This tremendously generated data is referred to as “Big data”. After scrutinized a lot of research work related to election prediction, a survey paper is presented in which every work related to election prediction using social media is incorporated. This paper is an attempt to review various tools, models, and algorithms used for the observation of campaign, discussion, prediction, and analysis of the election, and also suggest further tools and techniques for improvement.
Keywords: Social Media; Twitter; Election Prediction; Hadoop; Big Data; Parameters.